The Existence of Indonesian Language in Learning: Knowledge Manager in Elementary School - Amelia, Rizky; Dessy Dwitalia Sari; Rahmi Hidayati (Journal of Elementary School Education, 2023)
Indonesian is an important part of education. Indonesian as a knowledge manager in the 2013 curriculum has gone through a very long journey, since 1928 Indonesian has been the language of struggle. This understanding of language is in line with language education which has been championed by Indonesian due to the eroding sense of nationalism. The method of writing this article is literature study by exploring various scientific works related to this topic. The implementation of Indonesian as a knowledge manager in elementary schools is characterized by two opposite views. Pro views that Indonesian should be a science teacher in elementary schools, the approach in the 2013 curriculum that applies an integrative thematic is very appropriate for teaching text-based Indonesian. The counter view of the implementation of this policy is because the application of Indonesian in the 2013 curriculum does not involve much artistic values contained in literature. The essence of learning Indonesian is knowledge that must be given to students in order to teach them how to communicate well. Such communication can be made either orally or in writing, all to understand and respond to local, regional, national and global situations. This is one of the reasons learning Indonesian must be given at all levels of education, especially in elementary schools because it is the foundation of this learning.